Podocotyle nimoyi n. sp. (Digenea: Opecoelidae: Plagioporinae) and a re-description of Podocotyle pearsei Manter, 1934 from five species of deep-sea macrourids from the Gulf of Mexico and Caribbean Sea - Blend, Charles K.; Dronen, Norman O.; Armstrong, Howard W. (Zootaxa, 2016)
Two rare species of Podocotyle Dujardin, 1845 (Digenea: Opecoelidae) parasitizing five macrourid species inhabiting the deep waters of the northeastern Gulf of Mexico and Caribbean Sea off Panama are described. Podocotyle nimoyi n. sp. was found in the intestine of the pugnose grenadier, Sphagemacrurus grenadae (Parr), and the common Atlantic grenadier, Nezumia aequalis (Günther) (Gadiformes: Macrouridae), at depths of 534–995 m in the Northeast Gulf of Mexico off Florida and represents the fifth species of Podocotyle endemic to the deep sea. Podocotyle pearsei Manter, 1934, was re-described from the intestine of the bullseye grenadier, Bathygadus macrops Goode & Bean, the doublethread grenadier, Gadomus arcuatus (Goode & Bean), and the western softhead grenadier, Malacocephalus occidentalis Goode & Bean (Gadiformes: Macrouridae), collected from 591–728 m depths in the Northeast Gulf of Mexico off Florida and the Caribbean Sea off Panama. The following new host records are established: P. nimoyi n. sp. is the third parasite species known from S. grenadae and the first digenean species reported from this host; P. nimoyi n. sp. is the first reported species of Podocotyle parasitizing N. aequalis; and this is the first report of P. pearsei or any representative of the genus Podocotyle infecting B. macrops, G. arcuatus and M. occidentalis. A listing of all digenean parasites previously reported from the five macrourid species examined herein is given and some observations are made about Podocotyle in the deep sea.